Frequent occurrence of an intron 4 mutation in multiple endocrine neoplasia type 1. - Turner, J; Leotlela, P; Pannett, A; Forbes, SA; Bassett, J; Harding, B; Christie, P; Bowen-Jones, D; Ellard, S; Hattersley, A; Jackson, C; Pope, R; et al. (2002)
MEN1 is an autosomal dominant disorder characterized by parathyroid, pituitary, and pancreatic tumors. The MEN1 gene is located on chromosome 11q13 and encodes a 610-amino acid protein. MEN1 mutations are of diverse types and are scattered throughout the coding region, such that almost every MEN1 family will have its individual mutation. To further characterize such mutations we ascertained 34 unrelated MEN1 probands and undertook DNA sequence analysis. This identified 17 different mutations in 24 probands (2 nonsense, 2 missense, 2 in-frame deletions, 5 frameshift deletions, 1 frameshift deletional-insertion, 3 frameshift insertions, 1 donor splice site mutation, and a g-->a transition that resulted in a novel acceptor splice site in intron 4). The intron 4 mutation was found in 7 unrelated families, and the tumors in these families varied considerably, indicating a lack of genotype-phenotype correlation. However, this intron 4 mutation is the most frequently occurring germline MEN1 mutation ( approximately 10% of all mutations), and together with 5 others at codons 83-84, 118-119, 209-211, 418, and 516, accounts for 36.6% of all mutations, a finding that indicates an approach for identifying the widely diverse MEN1 mutations.